2013
DOI: 10.1016/j.juro.2012.08.083
|View full text |Cite
|
Sign up to set email alerts
|

Is a Sexual Dysfunction Domain Important for Quality of Life in Men with Urological Chronic Pelvic Pain Syndrome? Signs “UPOINT” to Yes

Abstract: Adding a sexual dysfunction domain to UPOINT may help improve quality of life in men treated for urological chronic pelvic pain syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 25 publications
6
32
0
2
Order By: Relevance
“…The modified UPOINTs algorithm has been suggested to support an optimized stratification of individual phenotypic profiles. However, clinical studies attempting to confirm an improved correlation between positive UPOINTs domains and symptom severity revealed heterogeneous results [48,[55][56][57].…”
Section: Treatment Of Chronic Prostatitis/chronic Pelvic Pain Syndromementioning
confidence: 99%
“…The modified UPOINTs algorithm has been suggested to support an optimized stratification of individual phenotypic profiles. However, clinical studies attempting to confirm an improved correlation between positive UPOINTs domains and symptom severity revealed heterogeneous results [48,[55][56][57].…”
Section: Treatment Of Chronic Prostatitis/chronic Pelvic Pain Syndromementioning
confidence: 99%
“…There may also be an association with recurrent UTIs in a minority of patients [19,21] Voiding LUTS (weak stream, straining and hesitancy) Storage LUTS (urgency AE urge incontinence, increased urinary frequency, nocturia and dysuria) Urethral burning during, and independent of, micturition Haematospermia (blood in semen) Recurrent UTI (more applicable to CBP) Sexual dysfunction symptoms [17,[22][23][24][25][26][27][28][29][30] Findings from cohort studies (n = 130-1 800) indicate that total or partial ED is reported by 15-55% of patients with CP/CPPS [22,[31][32][33][34], while the prevalence of overall, self-reported sexual dysfunction is higher at 46-92% [22,23,31,34]. Correlation studies of sexual dysfunction symptoms with NIH-CPSI scores indicate that patients with CP/CPPS with sexual dysfunction have higher total and QoL scores, suggesting that sexual symptoms can contribute substantially to morbidity [28,[31][32][33]35,36].…”
Section: Clinical Assessment and Diagnosismentioning
confidence: 99%
“…The clinical domains of UPOINT are Urinary symptoms, Psychosocial dysfunction, Organ-specific findings, Infection, Neurologic/systemic conditions, and Tenderness of muscles, providing mnemonic UPOINT. With sexual dysfunction affecting 40-70% of all men with CP/CPPS [39][40][41], the inclusion of an additional domain for sexual dysfunction was proposed, and a modified UPOINT algorithm (UPOINTs) has been suggested [42][43][44].…”
Section: Prudent Approach To Chronic Pelvic Pain In Malesmentioning
confidence: 99%